Marketing margin analysis of the Philippine mango industry price transmission and net margins - Aguinaldo, Roxanne T.
This paper aims to examine the Philippine mango industry by marketing margin analysis. It is an important tool in examining the benefits received by the different players in the chain in providing the demands of the customers. Two ways of examining such benefits are price transmission and net margins analyses. Price transmission analysis is a way of studying if changes in costs at the farm level have reflected the prices at the retail level. On the other hand, the study of net margins of the different players in the mango supply chain is a way of understanding not only the cost incurred by the players but also the benefits and profitability of the different players in the chain. Results of this study showed that price transmission elasticities are inelastic thus, the increase in the farm price is greater than the increase in the next node in the chain. This also implies that inefficiency exists in the mango supply chain. Different cases of chains from Davao City and Digos City were considered in this study. Results showed that among wholesalers and retailers in Davao City, retailers have the higher net margin. Consequently, among grower and wholesaler-retailer in Digos City, the latter receives greater benefits. Classification of mango increases the net margins of the players because of the differentiation in price.. The results of this study also showed that mango farmers owning only about 50-60 trees have no access to information. Furthermore, the analysis of the cost structure implies that there is uneven distribution of benefits along the chain. There were players in the chain who extracted benefits from other players to gain higher profit. The cost structure also implies that wholesalers have the buying power. Thus, inefficiency exists.